Novel and Efficient Synthesis of DHPMs Catalyzed by di‐DACH‐Pyridylamide Ligands. (26th September 2014) - Song, Qingbao; An, Xiaoxia; Che, Fengfeng; Shen, Tianhua
<x xml:space="preserve">Abstract</x> Di‐DACH‐pyridylamide ligands, symmetrical bridged bis‐Schiff base, and spiro pyrrolizines as catalysts in the synthesis of dihydropyrimidinethiones (DHPMs) using the Biginelli reaction is first reported. This new protocol has the advantages of environmental friendliness, short reaction time, excellent yields, and simple post‐treatment procedure. A series of DHPMs were obtained in high yields (up to 98%) in only 6 h. Moreover, based on the optimized condition, a novel Biginelli‐like reaction was first developed.